Combined novice, near-peer, e-mentoring palliative medicine program : a mixed method study in Singapore - Krishna, Lalit (2021)
Introduction: An acute shortage of senior mentors saw the Palliative Medicine Initiative (PMI) combine its novice mentoring program with electronic and peer mentoring to overcome insufficient mentoring support of medical students and junior doctors by senior clinicians. A three-phased evaluation was carried out to evaluate mentees' experiences within the new CNEP mentoring program. Methods: Phase 1 saw use of a Delphi process to create a content-valid questionnaire from data drawn from 9 systematic reviews of key aspects of novice mentoring. In Phase 2 Cognitive Interviews were used to evaluate the tool. The tool was then piloted amongst mentees in the CNEP program. Phase 3 compared mentee’s experiences in the CNEP program with those from the PMI’s novice mentoring program. Results: Thematic analysis of open-ended responses revealed three themes–the CNEP mentoring process, its benefits and challenges that expound on the descriptive statistical analysis of specific close-ended and Likert scale responses of the survey. The results show mentee experiences in the PMI’s novice mentoring program and the CNEP program to be similar and that the addition of near peer and e-mentoring processes enhance communications and support of mentees. Conclusion: CNEP mentoring is an evolved form of novice mentoring built on a consistent mentoring approach supported by an effective host organization. The host organization marshals assessment, support and oversight of the program and allows flexibility within the approach to meet the particular needs of mentees, mentors and senior mentors. Whilst near-peer mentors and e-mentoring can make up for the lack of senior mentor availability, their effectiveness hinges upon a common mentoring approach. To better support the CNEP program deeper understanding of the mentoring dynamics, policing and mentor and mentee training processes are required. The CNEP mentoring tool too needs to be validated.